2021
DOI: 10.1007/978-3-030-85440-9_9
|View full text |Cite
|
Sign up to set email alerts
|

Initial Insights into Exploratory Process Mining Practices

Abstract: Process mining enables organizations to streamline and automate their business processes. The initial phases of process mining projects often include exploration activities aimed to familiarize with the data and understand the process. Despite being a crucial step of many analyses, exploration can be challenging and may demand targeted guidance and support. Still, little attention has been paid to understanding how process analysts approach this exploratory phase. With this goal in mind, in this paper, we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…While the authors in [11] identify challenges like the insufficient domain expertise (C.20) or incomprehensible outcomes (C.16) and insufficient prescriptive capabilities of process mining tools (C.17) on the organizational level, the angle from which these challenges are covered differs from our findings and cannot be connected to the understanding of individuals. Based on our knowledge, there exists little support to help analysts guide their analysis based on the research question and reduce the risk of losing the analysis focus, and there is limited guidance for understanding event logs and data model structures [21]. Besides, the authors in [5] even observed that the thoroughness of reports for the stakeholder evaluation phase is decreasing in published case studies in the area of process mining.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the authors in [11] identify challenges like the insufficient domain expertise (C.20) or incomprehensible outcomes (C.16) and insufficient prescriptive capabilities of process mining tools (C.17) on the organizational level, the angle from which these challenges are covered differs from our findings and cannot be connected to the understanding of individuals. Based on our knowledge, there exists little support to help analysts guide their analysis based on the research question and reduce the risk of losing the analysis focus, and there is limited guidance for understanding event logs and data model structures [21]. Besides, the authors in [5] even observed that the thoroughness of reports for the stakeholder evaluation phase is decreasing in published case studies in the area of process mining.…”
Section: Discussionmentioning
confidence: 99%
“…Especially in the area of process mining [18], where specific algorithms are applied to event data to discover and improve (business) processes, the need for trained analysts familiar with different process mining tools is growing [9]. Although there is an increasing demand to attract analysts to work in process mining, little effort is made to better understand their ways of working [10] and particularly, how they approach the analysis phase [21].…”
Section: Introductionmentioning
confidence: 99%
“…The only paper so far that looks at process mining from an individual perspective is our previous work [22], which presents the results of a pilot study combining behavioral data and interviews to understand patterns and strategies of the initial exploration phase. In contrast, this paper, which is based on a newly collected data set, considers the whole analysis stage, focusing on strategies that analysts apply in their general work practices and considering factors and challenges affecting their use.…”
Section: Related Workmentioning
confidence: 99%
“…The closest work to ours is [14] and [27]. Klinkmüller et al [14] qualitatively analyze BPIC reports to understand how process analysts perform their work.…”
Section: Related Workmentioning
confidence: 99%